THE DEVELOPMENT OF DIGITAL SOCIOPRENEURSHIP IN INDONESIA AND ITS IMPLEMENTATION ON THE KITABISA.COM PLATFORM - Budiman Purba; muya syaroh; Amalia Sukma (Universitas Dharmawangsa Medan, 2025)
Social entrepreneurship is a form of entrepreneurship that is oriented towards achieving social goals through the realization of a vision, mission, and innovative ideas designed to address social issues. This practice generally starts on a limited scale, but can generate significant social and economic impact. Social entrepreneurs play an important role in providing alternative solutions to various social problems that have not been fully addressed by the public or private sectors. With the development of digital technology, various online fundraising or crowdfunding platforms have grown rapidly and made it easier for the public to channel and collect financial support. In this context, this study aims to analyze the development of sociopreneurship through the use of the crowdfunding platform Kitabisa.com. The results of this study are expected to broaden the understanding of the benefits and challenges faced by sociopreneurs in developing their social activities through the Kitabisa.com platform.